2019
DOI: 10.1177/0898264319890944
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Cohesion, Disorder, and Physical Function in Older Adults: An Examination of Racial/Ethnic Differences

Abstract: Objectives: This study examined the link between neighborhood social cohesion, disorder, and physical function in older adults, and identified potential racial/ethnic differences in these associations. Method: Data come from the National Health and Aging Trends Study (NHATS; N = 5,619). A series of linear regression models were used to predict physical function. Subgroup analyses and neighborhood/race interactions were used to examine differences. Results: Neighborhood disorder was associated with poorer physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…First, this is the first study that has examined the potential effect of the neighborhood environment on muscle mass and function in more than 2000 older adults (≥ 60 years old) as well as in males and females separately, using a longitudinal study design. Most previous studies on neighborhood environments and physical function included middle age adults, such as 40 or 50 years old together with older adults and most studies were cross-sectional [10][11][12][13][14][15][42][43][44][45]. Second, our study objectively measured both neighborhood environmental factors as well as muscle mass and function specific to sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, this is the first study that has examined the potential effect of the neighborhood environment on muscle mass and function in more than 2000 older adults (≥ 60 years old) as well as in males and females separately, using a longitudinal study design. Most previous studies on neighborhood environments and physical function included middle age adults, such as 40 or 50 years old together with older adults and most studies were cross-sectional [10][11][12][13][14][15][42][43][44][45]. Second, our study objectively measured both neighborhood environmental factors as well as muscle mass and function specific to sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood environments may be of importance particularly for older adults, who are likely to spend more time in their neighborhoods of residence than younger persons [9]. Several studies have examined the association between neighborhood environmental factors, e.g., safety, physical disorder (trash or littering), and social cohesion and older adults' physical functions such as activities of daily living [10][11][12][13][14]. One study from the US found that living in neighborhoods with high physical disorder, low social cohesion and low safety was associated with higher incidence of limitations in activities of daily living, such as getting across the room, bathing, eating and shopping for groceries [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both interviewers were trained in the use of questions from the systemic social observation survey [36]. Prior to entering the respondent's residence to conduct the interview, they each made an independent, confidential rating of the face-block using three items that focused on physical signs of graffiti, vandalism, and abandoned buildings [13,83]. The rating format for each item ranged from 0 (No, none present) to 3 (Yes, a considerable amount).…”
Section: Independent Variablementioning
confidence: 99%
“…The authors coined the term "Status Discord" to describe this phenomenon (23). Others have similarly posited that neighborhood disorder may be more detrimental to non-Hispanic Whites than non-Hispanic Blacks, but with a different rationale (24). The "epidemiological paradox" is described as a process by which marginalized racial/ethnic groups, given their greater exposure to disordered neighborhoods, develop greater coping and resilience and may thus fare better than their non-Hispanic White counterparts (24).…”
Section: Introductionmentioning
confidence: 99%